2007
DOI: 10.1063/1.2717561
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of oxidation and photo-oxidation of rubrene thin films by spectroscopic ellipsometry

Abstract: We follow in real-time and under controlled conditions the oxidation of the organic semiconductor rubrene grown on SiO2 using spectroscopic ellipsometry. We derive the complex dielectric function ε1 + iε2 for pristine and oxidized rubrene showing that the oxidation is accompanied by a significant change of the optical properties, namely the absorption. We observe that photo-oxidation of rubrene is orders of magnitude faster than oxidation without illumination. By following different absorption bands (around 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 11 publications
(16 reference statements)
4
79
0
Order By: Relevance
“…Earlier researchers have shown that illumination increases the oxidation of rubrene thin films. They also used a source of radiation in the UV to visible range 29,30 . After each exposure, the sample was characterized using XPS and UPS spectroscopies.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Earlier researchers have shown that illumination increases the oxidation of rubrene thin films. They also used a source of radiation in the UV to visible range 29,30 . After each exposure, the sample was characterized using XPS and UPS spectroscopies.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…We found that these data can be described very well using the optical constants of rubrene on silicon obtained by ellipsometry (and those of glass measured sep- arately with variable angle ellipsometry). The minor differences between the data and the model might be due to oxidation of some rubrene molecules in air [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…The data were analyzed based on established routines using a commercial software (WVASE32) 25,26 . In-situ X-ray reflectivity measurements (λ = 0.92Å) were performed similar to Ref.…”
Section: Methodsmentioning
confidence: 99%